The Influence of Startups in Increasing Entrepreneurship Awareness and Digital Literacy - Sabil, Sabil; Herjuna, Silvester Adi Surya; Hakim, Lukman; Suharmono, Soni; Utami , Eva Yuniarti (West Science Journal Economic and Entrepreneurship, 2023)
This research explores the influence of startups on raising entrepreneurship awareness and enhancing digital literacy in West Java. A mixed-methods approach was employed, combining quantitative surveys with qualitative in-depth interviews and focus group discussions. The study involved 300 respondents with diverse demographic characteristics, allowing for a comprehensive analysis of the startup ecosystem's impact. Quantitative findings revealed that a significant portion of the population in West Java has high levels of entrepreneurship awareness (40%) and digital literacy (35%). Moreover, 60% of respondents reported engagement with startups. Qualitative insights from interviews and focus group discussions emphasized the inspirational role of startups, their contribution to skill development, and the potential for collaboration between startups and educational institutions. The study also found that 75% of respondents perceived a positive influence of startups on entrepreneurship awareness and 70% on digital literacy. These findings underscore the critical role of startups in fostering entrepreneurship awareness and digital literacy in West Java. However, challenges such as resource limitations and the digital divide must be addressed to fully harness the benefits of startups.